EXPLORING THE INFLUENCE OF MOTIVATION ON THE FORMATION OF HEALTH-CONSCIOUS BEHAVIORS IN UNIVERSITY STUDENTS (Physical Culture and Sport: Scientific Perspective, 2025)
This article explores the role of motivation in shaping healthy lifestyle habits among student youth, with a focus on the significance of physical activity and physical education in this regard. Student youth constitute a vital segment of society, and their health directly influences the overall well-being of the nation and economic productivity. In light of the prevalent trends of physical inactivity among students, particularly in contemporary society, characterized by an abundance of stress factors and demanding mental workloads, the exploration of motivational factors that encourage physical exercise is of paramount importance.A review of extant approaches to the establishment of a healthy lifestyle reveals that motivation for physical activity constitutes the primary driving force in the formation of sustainable habits that contribute to students’ wellbeing. The study underscores the significance of cultivating interest in a healthy lifestyle through the implementation of motivational strategies that are tailored to the individual needs and interests of students. It is imperative to adapt physical education approaches considering the psychological characteristics of young people, their social context, and cultural factors. Innovative methods, such as digital technologies, mobile workout applications, and online courses, have been identified as key to enhancing motivation, especially in university education, where striking the right balance between academic activities and physical development is essential.The article presents a compelling argument for enhancing motivation to engage in physical activity, including the facilitation of access to sports facilities, the organization of sports competitions, and the promotion of a healthy lifestyle among students for their becoming vigorous participants and advocates of healthy living among their peers.The authors further emphasize that regular sports participation has been shown to contribute to physical development, as well as to cultivate qualities such as stress resistance, discipline, organization, and teamwork. These qualities are crucial for students' future professional success.
Keywords: motivation; healthy lifestyle; student youth; physical activity; physical education; innovative methods; higher education institutions